USE OF SPELLING PUZZLES AS A MEDIA FOR LEARNING VOCABULARY IN PRIMARY SCHOOL LEVEL STUDENTS - Safrina Junita; Haris Munandar; Qharina Safitri (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Vocabulary mastery is the initial stage in teaching elementary school studentsto understand basic Indonesian language mastery. Improving vocabularymastery in elementary school students can be done by using specific media, oneof which is the use of spelling puzzle media. This research aims to improvestudents' understanding of vocabulary through the use of spelling puzzle media.The type of research used in this research is the experimental method. Theresearch design will use one sample pretest-posttest researchdesign. The sampleused in this research was 20 grade 1 elementary school students. The results ofthe research show that there has been an increase in student learningcompleteness, where after implementing the posttest, student completeness was95%, after previously giving the pretest, the percentage of student completiononly reached 30%. This shows that the use of spelling puzzle media canincrease students' learning completeness related to elementary school levelstudents' vocabulary understanding in Indonesian language subject content.